2010
DOI: 10.1182/blood-2010-01-264390
|View full text |Cite
|
Sign up to set email alerts
|

The atypical chemokine receptor CCX-CKR scavenges homeostatic chemokines in circulation and tissues and suppresses Th17 responses

Abstract: Our previous in vitro studies led to proposals that the atypical chemokine receptor CCX-CKR is a scavenger of CCR7 ligand homeostatic chemokines. In the present study, we generated CCX-CKR ؊/؊ mice and confirm this scavenger function in vivo. Compared with wild-type mice, CCX-CKR ؊/؊ have a 5-fold increase in the level of CCL21 protein in blood, and 2-to 3-fold increases in CCL19 and CCL21 in peripheral lymph nodes. The effect of these protein increases on immunity was investigated after immunization with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 41 publications
4
103
3
Order By: Relevance
“…CCX-CKR plays an important role in controlling the migration of immune and cancer cells that express chemokine receptors CCR7 and CCR9, by reducing the availability of CCL19, CCL21, and CCL25 through internalization (8,10,11,15). CCX-CKR internalization was previously found to be independent of ␤-arrestins and clathrin-coated pits, as dominantnegative ␤-arrestin, Eps15 and Rab5 mutants did not impair CCL19 internalization in CCX-CKR-expressing HEK293 cells (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CCX-CKR plays an important role in controlling the migration of immune and cancer cells that express chemokine receptors CCR7 and CCR9, by reducing the availability of CCL19, CCL21, and CCL25 through internalization (8,10,11,15). CCX-CKR internalization was previously found to be independent of ␤-arrestins and clathrin-coated pits, as dominantnegative ␤-arrestin, Eps15 and Rab5 mutants did not impair CCL19 internalization in CCX-CKR-expressing HEK293 cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CCR7 and CCR9 have been shown to play a role in various cancers (9). CCX-CKR scavenges CCL19 and CCL21 both in vitro and in vivo, thereby decreasing the free concentration of these chemokines (7,8,10). Indeed, low CCX-CKR expression levels in breast cancer tumor cells were correlated with an increase in lymph node metastasis and consequently poor survival rate of patients (11).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…51 By producing CCX-CKR -/-mice, Comerford et al confirmed the function of these receptors under in vivo conditions. 52 CCX-CKR -/-rats compared to wild-type ones demonstrated 5-fold increase in the blood levels of CCL21 protein, and 2 to 3 times increase in CCL19 and CCL21 chemokines in the peripheral lymph nodes. In experimental autoimmune encephalomyelitis model (EAE), in CCX-CKR -/-mice compared to wild type, the disease developed faster and more intense, which was associated with an increase in CCL21 in the central nervous system (CNS).…”
Section: The Role Of Ccx-ckr In Autoimmune Encephalomyelitismentioning
confidence: 99%